Inclusive Design Elements in a Digital Storytelling Prototype for Dyslexic Children: A Thematic Analysis - Hassan Syauqi Ridzuan; Maizatul Hayati Mohamad Yatim; Nor Zuhaidah Mohamed Zain (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2026)
This study explores expert perspectives on the essential elements of a digital storytelling (DST) prototype designed to support early literacy among children with dyslexia. It aims to inform DST designers and educators in developing relevant content and potential design and implementation strategies for inclusive literacy learning. A qualitative design was employed using the Delphi method, involving iterative semi-structured interviews with seven subject-matter experts from special education, instructional technology, and multimedia fields. Data were analyzed using Braun and Clarke’s six-phase thematic analysis framework to generate themes systematically and ensure interpretive rigour. The findings revealed six interrelated themes emphasizing learner engagement, accessibility, pedagogical structure, content relevance, multimedia design, and teacher support. These themes indicate that experts indicated that future DST prototypes should combine clear instructional sequencing, dyslexia-friendly interface features, meaningful story content, and practical guidance for educators. The study highlights the need to integrate pedagogical, technological, and contextual considerations to enhance literacy development and engagement among dyslexic children. Overall, the study offers an empirically grounded framework for future DST development and promotes sustainable, equitable literacy interventions within inclusive educational settings.